Critical flicker frequency test for diagnosing minimal hepatic encephalopathy in patients with cirrhosis - Özel Coşkun, Banu Demet; Özen, Mustafa (Turkish Journal of Gastroenterology, 2017)
Abstract Background/Aims: The critical flicker frequency (CFF) and psychometric hepatic encephalopathy score (PHES) are commonly proposed tests for detecting minimal hepatic encephalopathy (MHE); however, no studies have examined their value for detecting MHE in Turkey. Materials and Methods: A total of 70 patients with cirrhosis without overt HE, 205 controls for PHES, and 100 controls for the CFF test were included. All the patients underwent the PHES and CFF tests during the same session. Psychometric tests comprising number connection test A and B, digit symbol test, serial dotting test, and line drawing test were used. Tests were considered abnormal when test score was more than mean ± 2 standard deviations in comparison with that of the age- and education-matched controls. MHE was diagnosed when ≥2 PHES test were abnormal, and CFF was <39 Hz. Results: The prevalence of MHE among the 70 patients with cirrhosis, as measured by the CFF and PHES tests, was 41.4% (29) and 30.7% (25), respectively. The mean CFF was significantly lower in patients with cirrhosis having MHE (38.3±1.2 Hz) than in patients with cirrhosis not having MHE (42.6±2.3 Hz; p=0.001) and in controls (44.84 ± 3.7 Hz; p=0.001). With a cutoff value of <39, CFF had a sensitivity of 39%, specificity of 82%, and diagnostic accuracy of 70.6% for detecting MHE. Conclusion: The CFF test is also a useful method for detecting MHE in xxx patients with cirrhosis. However, the CFF test should be used as an adjunct to the PHES test because of its low sensitivity for detecting MHE.